'I Am Doing a Double Thing. It Is For Me and It Is For Her': Exploring the Biographical Agency of Newcomer Immigrant and Refugee Youth. (September 2018) - Selimos, Erwin Dimitri
This article draws on 30 interviews conducted with newcomer immigrant and refugee youth in Canada to explore how they make sense of their migration and the consequences these meanings have on how they imagine their future selves. The article is based on the understanding that a key task of any immigrant is to negotiate the experiences of continuity and change indicative of the migration experience—a task that takes on unique contours for young immigrants who are simultaneously negotiating their transitions to adulthood. Analysis of the migration narratives of newcomer youth demonstrates that in making sense of their migration, young migrants draw on the general situation of their country of descent, their experiences of emigration and poignant intergenerational links to construct meaning of their lives in their new country of residence. These meanings orient their social actions and animate their life projects in their new host society.